Visualization robot sorter - Mohd Johaneis, Abu Bakar (2007)
At the present time, standard robot usages have a very large contribution for an industries and most of production is depend on it. By using this method, it will expand robotic function and developed a new technology for industries. Visualization Robot Sorter is a project that illustrates an arm robot graphic that move according to a voltages changes. A concept of rheostat is used for hardware compartment in collecting changes of voltage reading. Physically, the rheostat hardware is more to distance detector looks. For interfacing process, PCI – 1710 is used to dispatch the voltage changes data to computer program. LAbVIEW8.0 is a program that will visualize the arm robot movement and graph for voltage changes. There will be four differences type of movement that functions directly to the voltage changes. This design is expected to be useful since visualization program offers flexible usage and inspection process become easier.